Efeito da música na dor de recém-nascidos pré-termo submetidos à punção arterial - Farias, Leiliane Martins (2013)
Every day preterm infants (PI) are submitted to arterial puncture in the first hours of life for testing the gases and pH dosage. Although arterial puncture is painful, it is rarely accompanied by any analgesic measure. We Aimed to evaluate the effects of interventions: music, music and 25% glucose, and 25% glucose in relieving the pain of PI undergoing arterial puncture, and analyze the association of neonatal and therapeutic variables with the pain scores of PI obtained through the Premature Infant Pain Profile (PIPP). A cross-sectional randomized clinical trial of triple-blind experimental type, carried out at the Neonatal Care Unit (NCU) in a public hospital in Fortaleza-CE, Brazil, from November 2011 to August 2012. The sample consisted of 80 preterm infants, 24 randomized in Experimental Group 1 (EG1 – music); 33 in Experimental Group 2 (EG2 – music and 25% glucose); and 23 in Positive Control Group (PCG). Lullaby music was played for 10 minutes before arterial puncture through a MP3-player connected to earphones, for the infants in the EG1 e EG2, with 25% glucose administered to infants in the EG2 and PCG two minutes before arterial puncture. The primary outcome was the pain scores obtained with the PIPP in the first 240 seconds after the arterial puncture in an interval of 30 to 30 seconds. Secondary outcomes were the changes related to facial movements, Heart Rate (HR) and oxygen saturation (SpO2). This research was approved by the ethics committee under protocol No. 060 717/11. It was observed that the numeric neonatal variables of the PI in the EG1 versus total PIPP scores presented significant p in the variables: head circumference (HC – p=0.003), chest girth (CG – p=0.032), 1-minute Apgar (p=0.001), 5-minute Apgar (p=0.047), corrected gestational age (p=0.003), and corrected gestational age in days (p=0.008). In the EG2 versus total PIPP scores, p was significant in the variables: HC (p=0.002), 1-minute Apgar (p=0.009) and 5-minute Apgar (p=0.002). In the PCG versus total PIPP scores, p was significant in the variables: birth weight (p=0.045) and HC (p=0.027). Regarding therapeutic variables, PI had the highest concentration of PIPP scores among values ≥ 7 of moderate to severe pain. The therapeutic variable significant was the use of oxygen, with the Continuous Positive Airway Pressure (CPAP) as the most present in scores of moderate to severe pain (p=0.012) in the EG2. Regarding the total pain score measured in the three interventions through the PIPP, we observed a statistically significant difference in pain scores due to the intervention (p=0.000). The EG2 (57.6%) presented a higher percentage of minimal pain, ≤ 6, regarding the other groups, EG1 (29.2) and PCG (47.8). We conclude that it is considered valid the hypothesis that preterm infants submitted to the effects of music and 25% glucose, before and during arterial puncture, present lower pain scores compared to those that only use music or 25% glucose, with a difference of 1.5 points, according to the PIPP classification.